A year without "made in China" : - Bongiorni, Sara (John Wiley & Sons, 2007)
Journalist Bongiorni, on a post-Christmas day mired deep in plastic toys and electronics equipment, makes up her mind to live for a year without buying any products made in China, a decision spurred less by notions of idealism or fair trade-though she does note troubling statistics on job loss and trade deficits-than simply "to see if it can be done." In this more personal vein, Bongiorni tells often funny, occasionally humiliating stories centering around her difficulty procuring sneakers, sunglasses, DVD players and toys for two young children and a skeptical husband. With little insight into global economics or China's manufacturing practices, readers may question the point of singling out China when cheap, sweatshop-produced products from other countries are fair game (though Bongiorni cheerfully admits the flaws in her project, she doesn't consider fixing them). Still, Bongiorni is a graceful, self-deprecating writer, and her comic adventures in self-imposed inconvenience cast an interesting sideways glance at the personal effects of globalism, even if it doesn't easily connect to the bigger picture.